Feto-maternal outcome in human immunodeficiency virus seropositive mothers in co-relation with CD4 count - Trivedi, Swati; Nagar, Oby; Rastogi, Prasoon; Bhardwaj, Manish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: To study the effect of human immunodeficiency virus (HIV) infection on pregnancy outcomes and new born as mother to child transmission of HIV is a major route on new infections in children and compare it with HIV uninfected pregnancies. Methods: Prospective comparative study conducted on 40 HIV seropositive and 40 HIV seronegative pregnant women attending ANC and delivering in the department of obstetrics and gynecology, S. M. S. Medical College, Jaipur, Rajasthan, India. Results: CD4 count had no effect on birth weight of baby or term of delivery. HIV seropositive pregnancies were more prone to IUD, still birth and preterm birth (p=0.029). Mother to child transmission was 2.7%. Conclusions: HIV infection increases the risk of adverse foetal outcome in terms of intrauterine demise, still birth and preterm labour.